Should utility-reducing media advertising be taxed? - Hans Jarle Kind; Marko Köthenbürger; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2009)
Empirical evidence suggests that people dislike ads in media products like TV programs. In such situations standard economic theory prescribes that the advertising volume can be optimally reduced by levying a tax on ads. However, making use of recent advances in the theory of Industrial Organization and two-sided markets we show that taxing ads may be counterproductive. In particular, we identify a number of situations in which ad-adverse consumers are negatively affected by the tax, and we even show that the tax may lead to higher ad volumes. This unorthodox reaction to a tax may arise when consumers significantly dislike ads, i.e. in situations where traditional arguments for corrective taxes are strongest.
Keywords: D4; D43; H21; H22; L13; 330; Two-sided markets; media market; pricing strategy; ad-tax; Rundfunkwerbung; Werbebeschränkung; Steuer; Steuerwirkung; Medienökonomik; Lieferanten-Kunden-Beziehung; Medienverhalten; Betriebliche Preispolitik; Werbewirtschaft; Theorie